PENGARUH LINGKUNGAN KERJA, PELATIHAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. INDOMARET DI SUMBAWA BESAR NUSA TENGGARA BARAT - Askila, Wa Ode; Nuryani, Hanifa Sri (Jurnal Nusa Manajemen, 2024)
This research aims to examine the influence of the work environment, work training and work motivation on the performance of PT employees. Indomaret Sumbawa Besar branch, West Nusa Tenggara. The sampling technique used is the Census sampling technique, namely the number of samples is known. The research sample consisted of 86 employees spread across all Indomaret branches in Sumbawa Besar, West Nusa Tenggara. The analytical tool used in this research is multiple linear regression. The results of this research show that the Work Environment has a significantly positive effect on Employee Performance, JobTraining has a significantly positive effect on Employee Performance, and Work Motivation has a significant positive effect on Employee Performance.